2006
DOI: 10.1111/j.1365-2133.2006.07534.x
|View full text |Cite
|
Sign up to set email alerts
|

Nurse-led clinics reduce severity of childhood atopic eczema: a review of the literature

Abstract: The most effective way to manage atopic eczema is to provide adequate time for education and demonstration of treatments, which the literature suggests can be achieved through nurse-led clinics. The literature review supports an investigation researching the outcomes of a nurse-led clinic on reducing the severity of eczema in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 23 publications
1
55
0
1
Order By: Relevance
“…This pathway was been developed around the competences required to diagnose and optimally manage eczema 62 64. These competences have not been assigned to specific health professionals or settings in order to encourage flexibility in service delivery.…”
Section: Resultsmentioning
confidence: 99%
“…This pathway was been developed around the competences required to diagnose and optimally manage eczema 62 64. These competences have not been assigned to specific health professionals or settings in order to encourage flexibility in service delivery.…”
Section: Resultsmentioning
confidence: 99%
“…However, the algorithm was not superior to individual treatment by dermatologists so that the algorithm approach might not be needed in a dermatological setting. Notably, adequate management of AE does not only require effective anti-inflammatory treatment, but also the management of exacerbating factors and adjunctive treatment with emollients as well as sufficient patient education and instruction [1, 9, 19, 36, 53]. There is increasing evidence that nurse-led clinics for children with AE might be an effective and well-accepted alternative to conventional care from a doctor [53].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, adequate management of AE does not only require effective anti-inflammatory treatment, but also the management of exacerbating factors and adjunctive treatment with emollients as well as sufficient patient education and instruction [1, 9, 19, 36, 53]. There is increasing evidence that nurse-led clinics for children with AE might be an effective and well-accepted alternative to conventional care from a doctor [53]. Future studies should explore the acceptability, effectiveness, efficiency and ease of use of an algorithm-based treatment of AE in a large cohort of patients by means of a multi-disciplinary study including paediatricians, dermatologists, general practitioners and nurse-led clinics.…”
Section: Discussionmentioning
confidence: 99%
“…There is consensus among allergy experts that educational interventions should form part of the management of AE (Stalder et al, 2013). Time spent on the educational intervention is an important factor which impacts on the success of educating the parents (Moore, Williams, Manias, & Varigos, 2006). Alternative treatment: In a South African study by Stear (2011) it was found that more than half of the participants (general practitioners, specialists and dieticians) indicated that their patients were using complementary and alternative therapy before seeking conventional medical care, and that 43% were using this together with the medical treatment received from the participants.…”
Section: Literature Controlmentioning
confidence: 99%